Pengaruh Unique Products, Store Layout, dan Special Treatment Benefit Terhadap Customer Loyalty Pada Mixue Ice Cream and Tea Kota Mataram - Farizi, Zohdi Al; Dakwah, Muh. Mujahid (Postgraduate, University of Mataram, 2024)
This research aims to find out whether unique products, store layouts, and special treatment benefits affect customer loyalty in Mixue ice cream and tea in the city of Mataram. The research approach used is using quantitative methods. The sampling technique uses a non-probability sampling technique where samples are taken non-randomly with purposive sampling. The number of samples in this research was 100 respondents. The data collection method uses a survey sample, namely the distribution of questionnaires measured using a Likert scale and data analysis using the SPSS application. The results of this research show that the unique product variable has a positive and significant effect on the customer loyalty mix in Mataram City, the store layout variable has a positive and significant effect on the customer loyalty mix in Mataram City, and the Special Treatment Benefits variable also has a positive and significant effect on customers Loyalty Mixue Mataram City. Based on these results, it can be concluded that as a business actor, pay attention to the uniqueness, store layout and special treatment benefits of the products sold in order to attract the interest and attention of consumers make a purchase.